Electrochemical, microscopic and spectroscopic characterization of benzene diamine functionalized single walled carbon nanotube-cobalt (II) tetracarboxy-phthalocyanine conjugates - Mugadza, Tawanda; Nyokong, Tebello (Elsevier, 2016)
In this paper we report on the synthesis and characterization of 1,4-benzene diamine (BDA) functionalized single walled carbon nanotubes linked to cobalt (II) tetracarboxy-phthalocyanine. The characterization of the conjugate was through UV–vis, FTIR and X-ray diffraction (XRD) spectroscopies and by transmission electron microscope (TEM) and electrochemical methods. The conjugate is used for the electrochemical characterization of diuron. The catalytic rate constant for diuron was 4.4 × 103 M−1 s−1 and the apparent electron transfer rate constant was 18.5 × 10−6 cm s−1. The linear dynamic range was 1.0 × 10−5–2.0 × 10−4 M, with a sensitivity of ∼0.42 A mol−1L cm−2 and a limit of detection of 0.18 μM using the 3δ notation.